Christian missionary translation of the Qur’ān into Yoruba - Solihu, Abdul Kabir Hussain; Abdulhameed, Abdulganiy Akorede (2014)
Islam predated Christianity in Yorubaland in south-western Nigeria. Early Muslim preachers engaged in the cultural Islamisation of the followers of the Yoruba traditional religion as early as the Fourteenth Century. Christianity was introduced to Yorubaland some five centuries later in the first half of the Nineteenth Century. In their engagement with the local cultures, the Christian missionaries chose a course less traversed by their Muslim counterparts. The translation of the Bible into local vernacular languages is among the more common techniques employed by Christian missionaries in evangelization, particularly in Yorubaland. Yoruba is the first African language which the Bible was translated into by an indigenous, native speaker. Curiously, it was the Christian missionaries who also translated the Qur’ān into Yoruba, the first translation of the Qur’ān in an African language. Without question, Yorubaland was the centre of Muslim-Christian engagement in the Nineteenth Century. This paper deliberates on the emergence of the translated Qur’ān into the Yoruba language by the local Christian missionaries. It explores the theological bases and historical circumstances that led to the emergence of the Yoruba translation of the Qur’ān. The paper then provides an overview of the translations produced by Reverend Michael Samuel Cole in 1906 and Elijah Kola Akinlade in 1965.